2016
DOI: 10.1177/0267658316678286
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and working memory capacity: A comprehensive meta-analysis

Abstract: Bilinguals often outperform monolinguals on executive function tasks, including tasks that tap cognitive flexibility, conflict monitoring, and task-switching abilities. Some have suggested that bilinguals also have greater working memory capacity than comparable monolinguals, but evidence for this suggestion is mixed. We therefore conducted a comprehensive meta-analysis on the effects of bilingualism on working memory capacity. Results from 88 effect sizes, 27 independent studies, and 2,901 participants reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
139
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(170 citation statements)
references
References 78 publications
17
139
4
Order By: Relevance
“…It is hard to speculate why this research field presents such a mix of results based on the bilingual performances in working memory or executive functioning tasks, when well‐conducted meta‐analyses point in two completely directions (see Lehtonen et al , and Grundy & Timmer, ). However, the present study may offer a possible explanation to the diversity in the mixed findings along with other strengths, such as the sample characteristics offered by the Betula cohort study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hard to speculate why this research field presents such a mix of results based on the bilingual performances in working memory or executive functioning tasks, when well‐conducted meta‐analyses point in two completely directions (see Lehtonen et al , and Grundy & Timmer, ). However, the present study may offer a possible explanation to the diversity in the mixed findings along with other strengths, such as the sample characteristics offered by the Betula cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…An advantage for bilinguals over monolinguals in cognitive functioning has been observed in previous research (for reviews, see e.g., Bialystok, ; Bialystok, Craik & Luk, ). However, recent meta‐analysis of studies in cognitive performance in bilinguals have concluded both that this bilingual advantage doesn’t exist at all (Lehtonen, Soveri, Laine, Järvenpää, de Bruin & Antfolk, ) as well as that bilinguals gain a greater working memory capacity over time compared to monolinguals (Grundy & Timmer, ). Research has therefore aimed at identifying and controlling for other factors, such as cultural differences or immigrant status, and such factors have been suggested to vary across participant groups (Bak, ).…”
Section: Introductionmentioning
confidence: 99%
“…Learning and knowing a second language confers many benefits-economic (Agirdag, 2014;Rumbaut, 2014;Saiz & Zoido, 2005;Shastry, 2012), social (Morgan, 1993;Nelson, 1968), and academic (Cooper, 1987;Cooper et al, 2008;Dangiulli, Siegel, & Serra, 2001)-but recently there have been concerns over reputed cognitive benefits, particularly with regard to bilingual advantages in attention control (e.g., de Bruin, Treccani, & Della Sala, 2015;Hilchey & Klein, 2011;Paap, Johnson, & Sawi, 2015) and related abilities, such as working memory capacity (e.g., Ratiu & Azuma, 2015) in young adults. Many published investigations into the matter have observed a bilingual advantage (see Adesope, Lavin, Thompson, & Ungerleider, 2010;Grundy & Timmer, 2017), however, recent studies (Duñabeitia et al, 2014;Paap & Greenberg, 2013) and meta-analyses (Lehtonen et al, 2018;von Bastian, De Simoni, Kane, Carruth, & Miyake, 2017), have observed weaker and, in some cases, nonsignificant results (though see the following for arguments that a bilingual advantage does manifest in young adults as cortical reorganization and in older adults behaviourally: Bialystok, 2017;Bialystok & Grundy, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence is also mixed as to whether bilinguals may experience an advantage on measures of WMC specifically, although two recent meta‐analyses have found small to medium population effect sizes in favor of a bilingual advantage (Grundy & Timmer, ; von Bastian, De Simoni, Kane, Carruth, & Miyake, , November). However, both analyses also found considerable heterogeneity in effect sizes, with many studies included in the meta‐analyses demonstrating either no differences in performance between monolinguals and bilinguals or even bilingual disadvantages in performance.…”
mentioning
confidence: 99%
“…The research summarized above suggests several possibilities for how the modality of a WMC task might differentially affect bilingual and monolingual individuals. If bilingualism confers advantages in WMC (Grundy & Timmer, ; von Bastian et al, , November), then it is possible that a bilingual advantage could be observed for both oral and visual versions of the LNS task. However, there are several possible reasons to predict differences in LNS task performance for monolinguals and bilinguals depending on the modality of task administration.…”
mentioning
confidence: 99%